The Newest Digital Technologies in Education and The Prospects of Their Implementation in Ukraine - Kulish, Anatolii (2020)
The relevance of this article is due to the constitutional obligation of the state to provide the population with a high level of education. The purpose of the article is to carry out scientific research on the issue of educational digitization in developed countries of the world and to develop a program of educational digitization in Ukraine. The leading research methods are general scientific and specific research methods, including methods of logic, analysis, comparison and more. The results of this study are to outline the real need of modern society in the digitization of education, to determine the legal and organizational basis of such processes in the country, to develop an effective, step-by-step program for the digitization of education in Ukraine. The significance of the obtained results is reflected in the fact that this study can serve as a basis for outlining future changes to the current legislation of Ukraine on the issues of the digitization of education and reformatting the work of the relevant state bodies in the educational sphere.